The Christocentrism of Marian Homilies - Dyk, Stanisław (Verbum Vitae, 2024)
The aim of this article is to show the Christocentrism of Marian homilies. The starting point is to recall the fundamental function of the homily, which is to introduce the mystery of Christ, “always present and at work in us, especially in liturgical rites” (SC 35,2). This definition was applied to Marian homilies, revealing their three content areas: the proclamation of the mystery of Christ and Mary attested in the Word of God; the leading to participation in the grace of the mystery manifested in Mary and available in the liturgy; the call to conform oneself to Christ in imitation of Mary, his most faithful disciple. Those issues are explained and justified on the basis of Marian teaching of the Church and theological reflection. The analyses were also illustrated with the example of the Feast of the Immaculate Conception of the Blessed Virgin Mary. The analysis carried out in the study showed that the main axes around which the content of Marian homilies should be organised are the Christological, soteriological, liturgical and ecclesiological perspectives. The emphasis should be placed on ecclesiotypical rather than Christotypical Mariology. Such an approach to the Marian homily allows an organic view of Mary’s presence and modality in the history of salvation. It is at the same time an example of a liturgy-mystery-life synthesis integrating what is believed with what is celebrated and what is lived.